2020
DOI: 10.1007/s42995-020-00035-1
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between dietary marine components and intestinal flora

Abstract: The intestine is the natural habitat for a large and dynamic bacterial community, which perform vital metabolic and immune functions that significantly effect the nutritional and health status of the host. The major physiological functions of intestinal flora include metabolic activities that lead to important trophic effects on immune structure and function as well as protection of the colonized host against invasion by transient microbes. The intestinal flora is both a target for nutritional intervention and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 109 publications
0
8
0
Order By: Relevance
“…Multiple factors, including temperature, pH, diet composition and others, can affect the composition of gut microbial communities, and the modes of microbial transmission between an animal's gut and their environment is complex (Carmody et al ., 2015; Dill-McFarland et al ., 2015; Sylvain et al ., 2016; Fontaine et al ., 2018; Soriano et al ., 2018; Li et al ., 2020). As previous studies described, marine invertebrates can select specific environment microbes, and then form a gut microbial community which is different from the environmental microbial community ( C. gigas and R. philippinarum ) (Offret et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple factors, including temperature, pH, diet composition and others, can affect the composition of gut microbial communities, and the modes of microbial transmission between an animal's gut and their environment is complex (Carmody et al ., 2015; Dill-McFarland et al ., 2015; Sylvain et al ., 2016; Fontaine et al ., 2018; Soriano et al ., 2018; Li et al ., 2020). As previous studies described, marine invertebrates can select specific environment microbes, and then form a gut microbial community which is different from the environmental microbial community ( C. gigas and R. philippinarum ) (Offret et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…During the last decades, many studies have demonstrated that fucoidans extracted from brown seaweeds or marine invertebrates possess promising application prospect in marine functional foods owing to their various biological functions, including anti-oxidant, anti-inflammatory, anti-allergic, anti-tumor, anti-obesity, anti-coagulant, anti-viral, anti-hepatopathy, anti-uropathy, and anti-renalpathy activities ( Pradhan et al, 2020 ). In addition, fucoidans are considered as superior dietary fiber, which may be attributed to their functions of promoting gastrointestinal peristalsis and increasing the abundance of beneficial bacteria in the intestine ( Li, Xue, Zhang, & Wang, 2020 ). Fucoidans also play a positive part in adsorbing toxic substances (especially toxic heavy metals) in intestine, thereby reducing the harm of toxic substances accumulation ( Gao et al, 2020 ).…”
Section: Research Progress On Fcps and Fcosmentioning
confidence: 99%
“…in the intestine and the concentration of SCFAs in the colon, which has been proved to alleviate dyslipidemia and obesity caused by high-fat diet. Similarly, fucoidans extracted from Acaudina molpadioides are also effective in repairing the intestinal mucosal barrier damage caused by cyclophosphamide treatment through improving the expression of tight junction protein, promoting the production of SCFAs (particularly propionate and butyrate), and increasing the abundance of SCFAs-producing bacteria, such as Coprococcus , Rikenella , and Butyricicoccus species ( Li et al, 2020 ).…”
Section: Activities and Applications Of Fcepssmentioning
confidence: 99%
“…For example, they specifically promote the growth of beneficial intestinal species that produce high levels of bioactive metabolites ( Kasubuchi et al, 2015 ). Nowadays, seaweeds have attracted much attention for their rich diversified structures, various biological activities, and promising further application as functional foods; in particular, it is known to improve intestinal function ( Li et al, 2020 ; Otero et al, 2021 ). Recent studies have shown that seaweed polysaccharides can ameliorate high-fat diet (HFD)-induced metabolic syndromes by promoting the proliferation of beneficial intestinal microorganisms, for example, Akkermansia ( Shang et al, 2017 ; Guo et al, 2019 ; Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%